A look back, a path forward: Revisiting the mental health and well-being research and practice models and priorities in sub-Saharan Africa - Appiah, R. (New Ideas in Psychology, 2022)
Despite the enthusiasm to promote mental health in Ghana and sub-Saharan Africa more generally, the models and frameworks that underpin research and practice in these settings have focused exclusively on understanding and treating mental disorders, to the neglect of the mental health needs of the general, non-clinical population. We discuss the limitations of the bipolar and biomedical models as frameworks for mental health research and practice in the current paradigm. Using Ghana as a case example, we identify gaps in the mental health research priorities in sub-Saharan Africa, and discuss the limitations of the revised Mental Health Policy of Ghana in ensuring a mentally healthy population. Drawing on a consilience of evidence from the literature, we contend that, although important and laudatory, the current research approach and priorities, which remain overwhelmingly fixated on alleviating and treating symptoms of mental disorders, are insufficient to buffer against psychopathology and bolster positive mental health. We argue for the adoption of more global and empirically tested frameworks and population-based approaches to complement clinical approaches to reduce the population burden of mental health problems.
Research Article
Keywords: Mental health and well-being; Mental health policy of Ghana; Positive psychology